Children’s digital friendship practices during the first Covid-19 lockdown - Johansen, Stine Liv; Enemark Lundtofte, Thomas (MedieKultur: Journal of media and communication research, 2023)
During the Covid-19 pandemic, digital technologies have come to the forefront of mostpeople’s social, professional, and educational lives, and children have, like everyone else, depended on digital media for remote schooling as well as informal communication with their peers. This article presents results from a qualitative interview study among 20 Danish children, aged 3–12, and their parents during the spring and summer of 2020. As would be expected, age predicted a certain level of proficiency with, and access to, digital media technologies. However, children across the age spectrum of our sample relied on adult facilitation of digital practices in similar ways during a time where these were foregrounded in unforeseen ways. We discuss these findings in relation to a triadic theoretical framework of distributed agency, dynamic affordances, and access-oriented aspects of children’s practices with communication technology.